Perceived Barriers and Facilitators to Healthy Eating and School Lunch Meals among Adolescents: A Qualitative Study - Payán, Denise D. (Am J Health Behav, 2017)
OBJECTIVES: A qualitative research study was conducted to explore how perceived barriers and facilitators influence healthy eating and to investigate the acceptability of changes to school lunch meals among adolescents after implementation of the Healthy, Hunger-Free Kids Act of 2010. METHODS: Eight focus groups were conducted with adolescents (N = 64) at 3 South Los Angeles high schools. Data collection instruments included a semi-structured guide and questionnaire. Two researchers independently coded transcripts. RESULTS: Most participants believed fruits and vegetables were available in their community and reported high relative cost, poor quality, and lack of motivation as barriers to consumption. Many said school meals were an important source of healthy food and were aware of recent changes to the school lunch program. A primary facilitator to eating school lunches included access to fresh food items (eg, a salad bar). Perceived barriers included long cafeteria lines, time constraints, lack of variety, and limited quantities of preferred items. Off-campus food establishments near the school were viewed as competition to school meals. CONCLUSIONS: Our findings suggest the need to measure perceived and actual barriers to healthy eating among adolescents and to examine the effect of these barriers on dietary behavior. Programmatic and policy recommendations are provided.